The effect of transformational leadership and work motivation on work ethic - Helmina Br Ginting (Priviet Social Sciences Journal, 2022)
The role of human resources in advancing the company is very inportant. One approach to improve the quality of human resources is through the approach of a good Transformational Leadership and able to increase motivation, and therefore contributes to the work ethic of employee in PT. Pardic Jaya Chemicals. The purpose of this study is to analyze and explain the significant influence of work ethic, motivation and transformational leadership style toward employee performance in PT. Pardic Jaya Chemicals. The data were collected through questionares, through observation to the object research, processed further using descriptive analysis and Path analysis. The results of the analysis show that: (1) Transformational Ladership style has positive and significant effect toward Work Ethic, (2) motivation has positive and significant effect toward work ethic effect to employee performance, (3) Transformational Leadership and Motivation style has positive and sinificant effect toward work ethic on employee.